FISHERY POTENTIAL OF THE GULF OF KACHCHH - NAIR, VIJAYALAKSHMI R.; GOVINDAN, K.; RAMAIAH, NEELAM; GAJBHIYE, S. N. (Journal of Indian Fisheries Association, 2015)
Fishery potential of the interior Gulf of Kachchh and adjacent creek regions was reported for the first time as baseline data for future ecological assessment. The experimental trawling and gill netting indicated that the inner Gulf (ay.7.8 kg/h) was three times more productive than the creek (ay.2.3 kg/h). The number of species found in the Gulf and creek were respectively 34 and 20 suggesting good biodiversity of the living resources of the area.